PEMBUATAN DAN UJI KARAKTERISASI KOMPOSIT SERAT DAUN NANAS DENGAN RESIN EPOKSI SEBAGAI MATERIAL UNTUK KONSTRUKSI KAPAL - Elsa Shifa Auliya (2022)
In writing this final project, a research was conducted to determine the value of tensile strength and impact of natural fiber composite materials of pineapple leaves with epoxy resin, with alkalization treatment and variations in fiber size. It is hoped that this composite material can replace the use of synthetic fibers. The process carried out is to alkalize pineapple leaf fiber with 5% NaOH solution for 2 hours. Tensile and impact tests were performed using ASTM D-638-01 and D-5942-96 standards. From the results of the sample test, a tensile strength analysis was carried out which was then compared with the strength value required by the Indonesian Classification Bureau (BKI) as a benchmark for test standards. The results of the pineapple leaf fiber test with long fiber orientation have a greater tensile strength of 48.01 N/mm2 with a fiber composition of 35% and 65% resin, while for short fiber orientation it is 18.17 N/mm2. The tensile strength permitted by BKI is 98 N/mm2. The results of the impact test show that the long fiber orientation has a greater toughness value, namely 40.4x10-2 J/mm2, while the short fiber orientation has a toughness value that is still lower than the long fiber orientation, which is 4.1x10-2J/mm2